Policies for sustainable land management in the highlands of Tigray, northern Ethiopia - Gebremedhin, Berhanu; Pender, J.L.; Ehui, Simeon K.; Haile, M. (International Food Policy Research Institute, 2003)
The papers presented at this workshop dealt with a wide array of topics related to land management in the highlands of Tigray. The papers reported results on the causes and implications of agricultural change and land management; the status and determinants of soil fertility; land use; land transactions and impact of tenure security on land investment; policies and institutions for livestock development and sustainable land use; community woodlot and grazing land management; comparative analysis of community and private tree plantations; the economic return to and impacts of policies affecting land management; and the role of extension in sustainable land management in the region. This project characterises the problems of land management; identifies dominant pathways of development in the region and their causes; determines the past and current impacts of different factors on land management; strengthens the capacity of collaborating organisations in Tigray to conduct policy research and analysis related to land management; and helps facilitate adoption and implementation of policy and institutional strategies to improve land management in the highlands of Tigray.